Метод двобічних наближень у чисельному аналізі задачі Діріхле для нелінійного рівняння теплопровідності - Василишин, К. В. (ХНУРЕ, 2024)
A one-dimensional Dirichlet problem for the heat equation with an exponential heat conductivity coefficient and a heat sources function is considered. By replacing the unknown function, the problem under consideration was reduced to a problem for a semilinear differential equation, which was analyzed by methods of the operators theory in semi-ordered Banach spaces. Conditions for the existence of a single positive solution are obtained. The results of a computational experiment are presented.
Keywords: метод двобічних наближень; задача Діріхле; нелінійне рівняння теплопровідності